2003
DOI: 10.1007/s00442-003-1235-2
|View full text |Cite
|
Sign up to set email alerts
|

What determines host range in parasitoids? An analysis of a tachinid parasitoid community

Abstract: Despite the vast diversity of parasitic insects and their importance in natural and agricultural communities, our knowledge of what determines their patterns of association with hosts remains sparse. Unlike most parasites that tend to be specialized, parasitoid flies in the family Tachinidae exhibit a broad spectrum of host-specificity, with many species attacking a wide range of hosts. This variability in host-specificity makes them a useful model for examining the ecological and historical factors that deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
55
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 34 publications
1
55
1
1
Order By: Relevance
“…Reviews of the nature of tachinid host use have concluded that, as a whole, the family is generalist, and most variation on this pattern is due to a small subset of even more extremely generalist species (33). However, this conclusion is based almost entirely on host records from temperate regions and on generalist ''species'' as defined by their morphology.…”
Section: Discussionmentioning
confidence: 99%
“…Reviews of the nature of tachinid host use have concluded that, as a whole, the family is generalist, and most variation on this pattern is due to a small subset of even more extremely generalist species (33). However, this conclusion is based almost entirely on host records from temperate regions and on generalist ''species'' as defined by their morphology.…”
Section: Discussionmentioning
confidence: 99%
“…with broadly overlapping diets explains the coexistence of generalist herbivores in nature [11]. While this suggests that multiple generalist-specialist coexistence patterns can emerge in heterogeneous systems [9], the evolutionary processes involved in specialization are inevitably more complex when two or more resource dimensions influence the coexistence of species [12].…”
Section: Introductionmentioning
confidence: 99%
“…Host specificity has often been mentioned as a factor associated with adaptive specialization (Timms and Read 1999). Several attempts have been made to explain the patterns and processes of host specificity in different groups of parasites or parasitoids (see for instance Jaenike 1990;Poulin 1998;Š imková et al 2001a;Stireman and Singer 2003).…”
mentioning
confidence: 99%